Pengaruh Responsiveness Perawat Dalam Praktik Komunikasi Terapeutik Terhadap Kepuasan Pasien Di Ruangan Interna RSUD Dr. Hasri Ainun Habibie Provinsi Gorontalo - Molou, Avriliani Sagita (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The resource that contributes most to supporting patient satisfaction is nurses because they meet with patients more frequently in terms of providing health services. Therefore, communication is a fundamental thing needed in health services. The purpose of this researchcapable studentsdetermine the influence of nurse responsiveness in therapeutic communication practices on patient satisfaction at RSUD dr. Hasri Ainun Habibie, Gorontalo Province. Methods: . The research method used was descriptive research in the form of a case study on 10 respondents who were treated in the internal ward of RSUD dr. Hasri Ainun Habibie, Gorontalo Province. The results of this study show that the majority of patients are satisfied with the services provided by nurses at RSUD dr. Hasri Ainun Habibie, Gorontalo Province. Results: However, even though the majority of patients were very satisfied with the responsiveness provided by nurses at RSUD dr. Hasri Ainun Habibie, Gorontalo Province Conclusion: it was found from several statements contained in the questionnaire that most of the answer choices given were dissatisfied.